A Rush of Connections and Insights, a Glorious Moment of Clarity - Gary E. Davis; Mercedes A. McGowen (Networks: An Online Journal for Teacher Research, 2004)
For several years we have been interested in pre-service teachers' memory for mathematical episodes. Partly this is because memory is such a vital aspect of mathematical problem solving. Long-term declarative memory is the sort of memory involved when a person talks, writes, draws, or otherwise consciously represents their recollections. Warner, Coppolo & Davis (2002) identify long-term declarative memory as a key ingredient in flexible mathematical thinking - the ability to apply mathematical solution processes in different settings and across different representations - and Davis, Hill & Smith (2000) emphasize long-term declarative memory as a key feature in effective teaching of mathematics. Memory, broadly speaking, has three aspects: formation, storage and retrieval (Squire,1994). An aspect of memory that is of particular importance for this study is that of the "emotional color" of a memory. Le Doux (1998, 2002) has argued in recent years for the importance of emotional color in all aspects of memory, and Thurston (1997) alludes to colorizing his memory for written mathematics in order to "try to understand what it's really getting at rather than just what it says."